Ethnomathematics Tedhak Siten: Learning Design to Develop Student’s Critical Thinking Skill Based on Mobile Devices - Nuryadi, Nuryadi; Marhaeni, Nafida Hetty; Soviyati, Anik (Universitas Sebelas Maret, 2022)
Critical thinking is one of the essential skills in the 21st century that can be developed through learning mathematics, but in practice, there has not been much facilitation of learning media. Realistic mathematics learning by utilizing culture as well as integrating technology can be used as an ideal starting point for learning. This study aims to develop a mobile learning-based mathematics learning device with a realistic learning approach in the context of the Tedhak Siten ceremony to improve students' critical thinking skills. This type of research is development research that refers to the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). The data sources in this study were students and validators. The instruments used were the mobile learning application, the pretest, and posttest questions, the material expert validation questionnaire, the media expert validation questionnaire, and the student response questionnaire. The results showed that the validity aspect obtained a good category from the media expert validator and the material expert, the practical aspect of students as users obtained a good category, and the effectiveness aspect obtained a significant increase in pretest to posttest scores. So that learning mathematics with mobile learning applications can develop students' critical thinking skills and have potential effects.